Umbilical cord structural changes in Kenyan women with anemia diagnosed within the first 20 weeks of pregnancy: A retrospective cohort study. (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2025)
Background: Gestational anemia is a global health concern. The initial 20 weeks of pregnancy are critical for the development and prevention of negative pregnancy outcomes related to low hemoglobin levels. Objective: To compare the structural characteristics of the umbilical cord (UC) in women diagnosed with anemia in the first 20 weeks of pregnancy with those without anemia.Methods: This was a retrospective cohort study conducted at the Kenyatta National Hospital. Thirty-six umbilical cords were collected and examined for differences in gross and histological features. Comparisons were also made between the fetal and placental ends of the UC for these features.Results: Significant differences were observed in the diameter of the umbilical cord, the volume of Wharton’s jelly, and the intima-media thickness of the umbilical vein (all p